A case study of changes in muscle activity and power during the taper
Five junior national qualifiers were measured at five different times during a taper. Important swim meets were entered at the end of weeks three and four. After the fourth week, the swimmers covered a minimal distance as a post-season simulation. The daily distances were as follows: week 1 - 7,000; week 2 - 6,000; week 3 - 5,000; week 4 - 4,000; and week 5 - 3000 yards. During the first three weeks (which ended with a competition) power output on the swim bench, neuromuscular efficiency, recruitment of fast-twitch muscle fibers, hand forces, and propelling efficiency peaked. At the end of the fourth week the anaerobic contribution to performance peaked but by then the other measures had started to deteriorate. The swimmers' best performances occurred in the first swim meet (after three weeks of taper). In the following meet, performances were still good, but not of the standard of the previous week. Implications: In back-to-back competitions it may be difficult for age group swimmers to achieve personal best performances, articularly if a peaked taper is achieved for the first. The reader should be wary that this investigation evaluated only one form of taper and pre-competition preparation. There are many factors which need to be considered when peaking for a contest. It would be prudent to conclude that two important competitions on successive weekends may be beyond the capacity of age group swimmers to record personal best performances. Since the anaerobic contribution to swimming increased during the taper, it is suggested that the taper program contain a dedicated amount of anaerobic stimulation, particularly in sets that are swum at race pace. Those sets should be in addition to the exact sets of race pace and correct aerobic:anaerobic energy balance. The demonstration of three weeks of improvement shows that after an extended duration of hard training it is better to execute a long, rather than a short, taper.